The karyotypes of the thorny catfishes Wertheimeria maculata Steindachner, 1877 and Hassar wilderi Kindle, 1895 (Siluriformes: Doradidae) and their relevance in doradids chromosomal evolution - Eler, Eduardo Schmidt; Dergam, Jorge Abdala S.; Venere, Paulo Cesar; Paiva, Lílian C.; Miranda, Gabriela A.; Oliveira, Alessandro A. (Genetica, 2007)
We studied the karyotypes of two doradids, the rare and endangered Wertheimeria maculata and a derived Amazonian species, Hassar wilderi. Cytogenetic characterization was assessed using conventional staining (Giemsa), C-banding, and NOR banding. Both species had 2n = 58 chromosomes but differed in their chromosome formulae, 24 m + 14sm + 8st + 12a for W. maculata and 32 m + 16sm + 10st for H. wilderi. In W. maculata heterochromatin was mainly telomeric, and three chromosomes had a fully heterochromatic arm; in H. wilderi heterochromatin was also predominantly telomeric and evident in many more chromosomes. Hassar wilderi also presented one pair of homologues with a fully heterochromatic arm. In both species, nucleolar organizer regions were restricted to one pair of subtelocentric chromosomes. Assuming a basal position for W. maculata, we hypothesized that underlying conserved diploid and NOR-bearing chromosome numbers, chromosomal evolution in doradids has involved pericentric inversions and an increase of heterochromatic blocks. © 2006 Springer Science+Business Media B.V.
Keywords: Animals; Catfish; Chromosome; Female; Genetics; Karyotyping; Evolution, Molecular; Phylogeny; Animal; Catfishes; Chromosomes; Evolution, Molecular; Female; Karyotyping; Phylogeny; Doradidae; Hassar (catfish); Siluriformes; Wertheimeria